Processos de subjetivação em arte: cartografando poéticas de re-existência no grupo de crianças do serviço de convivência - Araújo, Tássya Bruna Galvão (2023)
Amid the context of the intersectionality of structural oppressions of class, gender and race that constitute Brazilian society and that are expressed in the demands of Social Assistance policy, we bet on a policy with openness to sharing experiences in the field of affections, sensibilities, of becomings. We think of art as aesthetics, poetics of re-existence that problematizes an established reality, placing itself before it as modes of recreation. How does life affirm and reaffirm itself and reinvent itself in the face of social adversity? What territories of childhood are produced in the art of collective meetings, in coexistence as a space of self in the world, in the relationship with Social Assistance? Thus, this research has the general objective of mapping processes of subjectivation in art in the Coexistence and Strengthening of Bonds Service-SCFV with children. The research subjects are children aged between 6 and 9 years old, who participate in the aforementioned service that is offered by the Social Assistance Reference Centers, the CRAS. With the following specific objectives: a) Map ways of doing and feeling in the practices of the Coexistence Service (what happens, how it happens) b) Analyze childhood territories in their relationship with the Social Assistance Policy c) Problematize vulnerability policies, based on collective and poetic constructions of re-existence with children. As a methodological path, we were inspired by qualitative cartographic research, defined as intervention research in the process of monitoring subjectivation processes, the movements and forces that cross the modes of existence. We relied on the preparation of field diaries, and we proposed workshop moments, based on the poetic device of art as experiments on sensibilities and collective productions. Schizoanalysis and Institutional Analysis are theoretical movements that inspired us in the production of analyses. We experienced the power of these meetings with regard to the production of creative ways of implementing public Social Assistance policy in its relationship with children. It is in the possibility of inventing the condition of experience of becoming-child that the Coexistence Service becomes becoming-art. It deterritorializes itself from the fixity of machines that produce rigidity and opens up to the composition of territories that enhance joyful and inventive encounters. The SCFV proves to be a powerful territory for what encounters between the different agents of established coexistence can produce on the level of difference.